SINKRONISASI TATA CARA PENCALONAN, PEMILIHAN DAN PELANTIKAN KEPALA PEMERINTAH NEGERI DI KABUPATEN MALUKU TENGAH - Lainsamputty, Natanel (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
ABSTRACT Dynamics The development of the village government system has undergone substantial changes with the issuance of Law Number 6 of 2014 concerning Villages. The regulation regarding the election of village heads has changed with a simultaneous election mechanism and the candidate who gets the most votes has the right to be appointed as village head. The purpose of this study is to examine and analyze the regulation with the election mechanism in the district of Central Maluku which in the Regional Regulation Number 03 of 2006 concerning Procedures for the Nomination, Election and Inauguration of the Head of the Negeri Government which the substance of the article on elections still refers to Law Number 32 of 2014 which is no longer valid, the regulation needs to be synchronized so that the application of the existing rules does not conflict with higher rules or positive rules. The method used in this research is a normative method with a study approach with primary data that refers to the applicable regulations and then dissected with secondary data based on concepts, theories and principles in the formation of legislation. Keywords: Synchronization, Regional Regulations, Village Head Elections